(untitled) (Research in Agriculture Livestock and Fisheries, 2026)
This study investigates the livelihood status of 100 randomly selected fishermen and stakeholders in Kawran Bazar, Dhaka, and Trishal, Mymensingh, using structured interviews and focus group discussions conducted in 2025. Results show that 48.25 of respondents fall within the 31-50 age bracket. Demographically, 70% are Muslim, while 41% live in nuclear families, with 55% maintaining a joint family. Educational attainment is low 44% HSC passed; 59% SSC, and 11% fishermen can sign. While fishing is the primary source of income, many supplement this income through agriculture (51%), labor (30%), or net-making. Living conditions reflect significant hardship: 80% and 87% reside in katcha houses, with 20% and 13% in semi-paccha houses. Sanitation challenges are evident: 3% use open fields for toilets, 70.5% use katcha latrines, 27% use open holes, and 59% use latrines. Collectively, these findings highlight a precarious socio-economic environment. Improving these conditions is vital not only for the well-being of the fishing community but also for the sustainable management of local fisheries biodiversity. Addressing gaps in education, healthcare, and sanitation through targeted policy interventions is essential to fostering a more resilient and productive aquatic ecosystem in Bangladesh. Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 219-232